0709 Racial Differences in Objective and Subjective Sleep Parameters: A Sample of Inner-City Women. (27th April 2018) - Fischer, A; Aranda, F; Lillis, T A; Burgess, H J; Burns, J W; Purim-Shem-Tov, Y; Hobfoll, S E
Abstract: Introduction: African Americans (AA) are increasingly recognized as a population with significant sleep inequities. This study examined racial differences in objective and subjective sleep parameters from a diverse sample of inner-city women who presented to an urban Emergency Department (ED) with an acute pain complaint. Methods: As part of an ongoing, longitudinal study examining the relationship between pain and traumatic stress, seven days of wrist actigraphy, and sleep diaries were collected from 44 women. The mean age of the women was 29.41 years (SD = 6.00); race/ethnicity was 41% AA, 39% Latina, 11% White, and 9% Other. Total sleep time (TST), wake after sleep onset (WASO), sleep efficiency (SE) and fragmentation (FRAG) were estimated with actigraphy; sleep quality (SQ) ratings, and number of perceived awakenings were collected via self-report from the Consensus Sleep Diary. Results: The sample was divided between AA race (n = 18) and Non-AA race (n = 26) following preliminary analysis that found no significant differences in primary study variables (e. g. TST, SQ) among Latina, White, or Other race/ethnicity. A series of one-way ANOVAs based on AA race relative to Non-AA race revealed significant differences in most objective variables including significantly lower values for TST (F = 6.57), and SE (F = 4.12), higher values for FRAG (F = 7.17), but no significant differences were found based on subjective measures (all p's < .05). These differences were not accounted for in pain intensity/interference, PTSD symptoms, education, or employment status. However, AA women were more likely to have lower incomes than non-AA women. Conclusion: The results indicate that AA women appear to have shorter, more fragmented sleep compared to Non-AA women yet no difference in subjective sleep quality ratings. Additionally, AAs have significantly lower incomes which could indicate a social determinant of sleep with varying influence on objective and subjective sleep parameters. As the present study continues data collection, a follow-up will be presented to provide additional information on race/ethnicity differences in objective and subjective sleep parameters. Support (If Any): 3R01DA039522-02S1.